The Effectiveness of Private Sector Development Interventions in Fragile and Conflict-Affected Situations : Evidence from Evaluations - Liu, Chaoying; Harwit, Emily (International Finance Corporation, Washington, D.C., 2017)
This systematic review is an effort to fill the knowledge gap about the effectiveness of PrivateSector Development (PSD) interventions in Fragile and Conflict-Affected Situations (FCS). Theobjective of the review is to identify and extract evidence from published evaluations of PSDinterventions in FCS on what has or has not worked in terms of achieving development results,including contributions to peace and stability. The review identified 312 published evaluations of PSD interventions carried out between 2005 and 2014, of which 56 constituted the final data set for the review analysis. The review covered evaluations in 23 countries classified as FCS by the World Bank from 2005-14 and three other countries that experienced conflict. Annex 1 shows how each of the 23 countries were categorized according to the country’s conflict status from the FCS list. In summarizing the evidence, we defined ‘effectiveness’ as how external evaluators measuredthe degree of success in attaining the planned results and objectives of PSD projects in FCS.Project effectiveness was measured within four business lines: SME support, infrastructure,access to finance and investment climate reform. The evaluability, or the ability of evaluators to determine how well projects were implemented, was weak in some projects under review. For example, in 25 percent of the evaluated projects, outcomes were either poorly defined or not appropriate. In addition, the basis for determining success across individual projects was not always clear because projects sometimes defined outputs and outcomes differently, even when long and short-term results were achieved. This limited our ability to appropriately catalog the projects’ evidence in a consistent and clear manner.